Physical fitness and activity, metabolic profile, adipokines and endothelial function in children - Jociene Terra da Penha; Fernanda Mussi Gazolla; Cecília Noronha de Miranda Carvalho; Isabel Rey Madeira; Flávio Rodrigues‐Júnior; Elisabeth de Amorim Machado; Fernando Lencastre Sicuro; Paulo Farinatti; Eliete Bouskela; Paulo Ferrez Collett‐Solberg (Brazilian Society of Pediatrics, 2019)
Objectives: The prevalence of obesity is increasing. The aim of this study was to investigate if there is endothelial dysfunction in children with normal or excess weight, and whether the metabolic profile, adipokines, and endothelial dysfunction would be more strongly associated with physical fitness or with physical activity levels. Method: Cross‐sectional study involving children aged 5-12 years. The evaluation included venous occlusion plethysmography, serum levels of adiponectin, leptin and insulin, lipid profile, physical activity score (PAQ‐C questionnaire), and physical fitness evaluation (Yo‐Yo test). Results: A total of 62 children participated in this study. Based on the body mass index, 27 were eutrophic, 10 overweight and 25 obese. Triglycerides, LDL cholesterol, HOMA‐IR, and leptin were higher in the obese and excess‐weight groups compared to the eutrophic group (p < 0.01). HDL cholesterol and adiponectin levels were higher in the eutrophic group compared to the obese and excess‐weight groups (p < 0.01). Flow‐mediated vasodilation after hyperemia was higher in the eutrophic group in comparison to obese and excess‐weight subjects (p < 0.05). There was no difference in the physical activity levels among groups measured by PAQ‐C. The Yo‐Yo test was significantly associated with HDL cholesterol (rho = −0.41; p = 0.01), and this association remained after adjusting for body mass index z‐score (rho = 0.28; p = 0.03). Conclusion: This study showed that endothelial dysfunction is already present in obese children, suggesting a predisposition to atherosclerotic disease. Moreover, HDL cholesterol levels were correlated with physical fitness, regardless of body mass index. Resumo: Objetivos: A prevalência da obesidade está aumentando. O objetivo deste estudo foi investigar se há disfunção endotelial nas crianças com peso normal ou excesso de peso e se o perfil metabólico, as adipocinas e a disfunção endotelial seriam mais fortemente associados à aptidão física ou aos níveis de atividade física. Método: Estudo transversal que envolve crianças de 5‐12 anos. A avaliação incluiu pletismografia de oclusão venosa, níveis séricos de adiponectina, leptina, insulina e lipidograma, escore de atividade física (questionário PAQ‐C) e avaliação da aptidão física (teste Yo‐yo). Resultados: Um total de 62 crianças participou deste estudo. Com base no índice de massa corporal, 27 eram eutróficos, 10 estavam acima do peso e 25 estavam obesos. Os níveis de triglicerídeos, colesterol LDL, HOMA-RI e leptina estavam mais elevados nas crianças obesas e com excesso de peso que o grupo de eutróficos (p < 0,01). Os níveis de colesterol HDL e adiponectina estavam mais elevados no grupo de eutróficos em comparação ao grupo de obesos e com excesso de peso (p < 0,01). A vasodilatação mediada pelo fluxo após hiperemia foi maior no grupo de eutróficos em comparação aos indivíduos obesos e com excesso de peso (p < 0,05). Não houve nenhuma diferença nos níveis de atividade física entre os grupos medidos pelo PAQ-C. O teste de ida e volta foi significativamente associado ao colesterol HDL (ró = −0,41; p = 0,01) e essa associação continuou após ajustar o escore z do índice de massa corporal (ró = 0,28; p = 0,03). Conclusão: Este estudo mostrou que a disfunção endotelial já está presente nas crianças obesas, sugeriu uma predisposição à doença aterosclerótica. Além disso, os níveis de colesterol HDL foram correlacionados à aptidão física, independentemente do índice de massa corporal. Keywords: Obesity, Endothelial dysfunction, Cardiovascular disease, Obesity, Overweight, Pediatrics, Palavras‐chave: Obesidade, Disfunção endotelial, Doença cardiovascular, Obesidade, Sobrepeso, Pediatria